The Mediating and Moderating Roles of Life Skills and Cortisol in the Relationship Between Sleep Quality and Depressive Symptoms Among Chinese Adolescents With Childhood Household Dysfunction - Mao, Ping; Peng, Lianhua; Yuwen, Weichao; Liu, Dongdong; Yan, Fang; Chen, Yang; Long, Yixiang; Hash, Jonika (Frontiers in Psychiatry, 2022)
Background: Various studies show that sleep quality, life skills, and cortisol are associated with depressive symptoms, separately. However, the relationships between sleep quality, life skills, cortisol, and depressive symptoms remain unclear. Thus, this study aims to examine the mediating or moderating roles of life skills and cortisol in the relationship between sleep quality and depressive symptoms. Methods: A retrospective cross-sectional study was performed among 212 adolescents with childhood household dysfunction (CHD) from August to October 2020 in China. We used the Pittsburgh Sleep Quality Index, the Secondary School Student Life Skills Rating Scale, and the Center for Epidemiologic Studies Depression Scale to measure sleep quality, life skills, and depressive symptoms, respectively. Additionally, 65 participants provided blood samples to assess their blood cortisol levels. Analyses included correlations, regressions, and structural equation models. Bootstrapping was performed to examine the mediation effect. Multiple regression analysis was performed to examine the moderation effect. Results: The results showed that sleep quality and life skills were significantly associated with depressive symptoms (p < 0.01). Life skills mediated and moderated the relationship between sleep quality and depressive symptoms. Cortisol moderated the relationship between sleep quality and depressive symptoms. Conclusions: Our findings support potential mediating and moderating roles of life skills and cortisol in the relationship between sleep quality and depressive symptoms, which suggests improving sleep quality, life skills are of great significance in the prevention and intervention of depression in adolescents with CHD, and disseminating knowledge about the high risk of developing increased depressive symptoms among adolescents with CHD with higher cortisol levels is indicated.